The effect of CEOs on firm performance - Mackey, Alison (Strategic Management Journal, 2008)
Abstract The extent to which CEOs influence firm performance is fundamental to scholarly understanding of how organizations work; yet, this linkage is poorly understood. Previous empirical efforts to examine the link between CEOs and firm performance using variance decomposition, while provocative, nevertheless suffer from methodological problems that systematically understate the relative impact of CEOs on firm performance compared to industry and firm effects. This study addresses these methodological problems and reexamines the percentage of the variance in firm performance explained by heterogeneity in CEOs. The results of this study suggest that in certain settings the ‘CEO effect’ on corporate‐parent performance is substantially more important than that of industry and firm effects, but only moderately more important than industry and firm effects on business‐segment performance. Copyright © 2008 John Wiley & Sons, Ltd.